Correction: Differential expression of sulfate transporters under selenium supply identifies OsSULTR1;1 as a candidate for nutritional enhancement in super basmati rice - Noreen Aslam; Muhammad Sameeullah; Songul Gurel; Ekrem Gurel (Molecular Biology Reports, 2026)

Differential expression of sulfate transporters under selenium supply identifies OsSULTR1;1 as a candidate for nutritional enhancement in super basmati rice - Noreen Aslam; Muhammad Sameeullah; Songul Gurel; Ekrem Gurel (Molecular Biology Reports, 2026)

Comparative Chloroplast Genomics of Sugar Beet and Wild Relatives: Insights into Photosystem Gene Regulation and Stress Tolerance - Muhammad Sameeullah; Abdullah; Neelam Batool; Ibrar Ahmed; Mehmet Cengiz Baloglu; Noreen Aslam; Mehmet Örgeç; Ekrem Gurel; Mohammad Tahir Waheed; Songul Gurel (Functional & Integrative Genomics, 2026)

AMF and Trichoderma Confer Cereal Cyst Nematode ‘Heterodera filipjevi’ Resistance in Wheat by Fine-tuning Ionomics, Metabolomics, and Transcriptomics - Özgenur Arslanoğlu; Muhammad Sameeullah; Ayşegül Yaman; Nagihan Duman; Furkan Ulaş; Ebubekir Yüksel; Mustafa İmren; Abdelfattah A. Dababat (Journal of Plant Growth Regulation, 2026)

Comparative Analysis of Two Wheat Cultivars under Iron Deficiency: Integrating Morphological, Physiological, Anatomical, Molecular, and Yield Responses to Reveal Destan’s Resilience - Muhammad Sameeullah (Journal of Plant Growth Regulation, 2026)
Iron (Fe) deficiency is a major constraint to wheat productivity in calcareous soils, necessitating the identification of cultivars with improved Fe-use efficiency. This study compared two Turkish bread wheat cultivars, Destan and Reis, under Fe-deficient (2 µM) and Fe-sufficient (50 µM) conditions to elucidate morphological, physiological, anatomical, ionomic, and molecular responses associated with Fe efficiency. Although Destan exhibited higher baseline growth under Fe sufficiency, its response to Fe limitation was characterized by a smaller reduction in several physiological and growth-related traits relative to Reis. Under Fe deficiency, Destan maintained higher chlorophyll content, biomass, root system development, and shoot Fe concentration than Reis. Ionomic analysis revealed coordinated enrichment of Fe along with Zn, Cu, Ni, K, and Ca in Destan, whereas Reis showed disrupted mineral homeostasis. Anatomical observations demonstrated enhanced root hair formation, preserved endodermis thickness, and distinct vascular organization in Destan under Fe deficiency, suggesting improved internal transport regulation. At the molecular level, Destan showed strong induction of Strategy II iron acquisition genes, including Zinc-Induced Facilitator-Like 4 ( TaZIFL4 ), Nicotianamine Synthase 3 ( TaNAS3 ), and Nicotianamine Aminotransferase 1 ( TaNAAT1 ), whereas Reis exhibited weaker activation of these pathways. Bromocresol purple assays indicated limited rhizosphere acidification in Destan, consistent with a Strategy II-dominant Fe uptake mechanism in wheat. However, Destan exhibited a greater proportional decline in grain yield under Fe-deficient conditions compared with Reis, indicating lower yield stability despite its stronger physiological and molecular responses. Collectively, these results indicate that Destan displays a more integrated and efficient Strategy II-based response to low Fe availability, highlighting its potential for improving Fe acquisition mechanisms, although yield stability under Fe deficiency requires further consideration.

Artificial intelligence applications in abiotic and biotic plant stress management: A comprehensive bibliometric and literature review - Furkan Ulaş; Rachid Lahlali; Salah-Eddine Laasli; Muhammad Aasim; Abdelfattah Dababat; Muhammad Sameeullah; Mustafa İmren (Physiological and Molecular Plant Pathology, 2026)

Decoding genetic diversity and population structure of Brassica species by inter primer binding site (iPBS) retrotransposon markers - Muhammad Sameeullah; Fatma Kayaçetin; Khalid Mahmood Khavar; Achmad Yozar Perkasa; Siti Maesaroh; Mohammad Tahir Waheed; Vahdettin Çiftçi (Genetic Resources and Crop Evolution, 2025)
Marker-assisted breeding serves as a potent tool for screening target germplasm, assessing genetic diversity, and determining breeding potential of a crop. Therefore, inter primer binding site (iPBS)-retrotransposons marker system was employed to evaluate a collection of 33 Brassica genotypes, including 10 Brassica juncea , 5 B. oleracea , 7 Sinapis alba , 5 B. nigra , and 6 B. rapa , were utilized to evaluate their genetic diversity and variations 10 polymorphic primers that generated a total of 144 bands. Various diversity indices were calculated in the studied germplasm, including polymorphism information content (0.13–0.30), effective number of alleles (1.217–1.689), Shannon’s information index (0.244–0.531), and gene diversity (0.148–0.370). These indices collectively affirmed substantial genetic variations within the germplasm. Molecular variance analysis revealed that the majority (62%) of genetic variations were present within populations. The Brassica accessions were categorized into three populations utilizing a model-based structure algorithm. Evaluation of diversity indices based on the structure indicated that populations III and II exhibited higher diversity. Principal coordinate analysis and neighbor-joining analysis further corroborated the three distinct populations, confirming the reliability of the STRUCTURE analysis. Notably, the genetic distance assessment identified BN1 and BN3 from B. nigra species and the genotypes BO1 and BO3 from B . oleracea as genetically diverse mustard accessions. The extensive genetic diversity observed within the Brassica germplasm underscores its significance as a valuable genetic resource for comprehensive Brassica breeding programs. Moreover, these accessions hold promise as suitable candidates for heterosis breeding initiatives aimed at improving mustard production.

Isolation of the 3β-HSD promoter from Digitalis ferruginea subsp. ferruginea and its functional characterization in Arabidopsis thaliana - Noreen Aslam; Muhammad Sameeullah; Muhammet Yildirim; Mehmet Cengiz Baloglu; Buhara Yucesan; Andreas G. Lössl; Mohammad Tahir Waheed; Ekrem Gurel (Molecular Biology Reports, 2022)

An efficient regeneration system and steviol glycoside analysis of Stevia rebaudiana Bertoni, a source of natural high-intensity sweetener - Buhara Yücesan; Refik Büyükgöçmen; Aliyu Mohammed; Muhammad Sameeullah; Cevher Altuğ; Songül Gürel; Ekrem Gürel (In Vitro Cellular & Developmental Biology - Plant, 2016)

In vitro propagation and cardenolide profiling of Digitalis ferruginea subsp. schischkinii, a medicinally important foxglove species with limited distribution in Northern Turkey - Buhara Yücesan; Aliyu Mohammed; İsmail Eker; Muhammad Sameeullah; Öznur Demir-Ordu; Cansu Cihangir; Nevin Şahbaz; Özge Kaya; Frieder Müller-Uri; Wolfgang Kreis; Ekrem Gürel (In Vitro Cellular & Developmental Biology - Plant, 2016)

Recent developments in therapeutic protein expression technologies in plants - Shah Fahad; Faheem Ahmed Khan; Nuruliarizki Shinta Pandupuspitasari; Muhammad Mahmood Ahmed; Yu Cai Liao; Muhammad Tahir Waheed; Muhammad Sameeullah; Darkhshan; Saddam Hussain; Shah Saud; Shah Hassan; Amanullah Jan; et al. (Biotechnology Letters, 2015)